Admissions and outcomes after perinatal asphyxia and hypoxic-ischaemic encephalopathy before and after therapeutic hypothermia: a retrospective population-based study - Karoline Aker; Ragnhild Støen; Miriam Martinez-Biarge; Janicke M Syltern (BMJ Paediatrics Open)
Background Hypoxic-ischaemic encephalopathy (HIE) is the leading cause of brain injury in term infants, and therapeutic hypothermia (TH) has been shown to improve outcomes for infants with moderate/severe HIE. We aimed to describe admission rates and outcomes after perinatal asphyxia and HIE before and after the implementation of TH in June 2007.Methods This single-centre, retrospective, population-based study included term/near-term infants born between January 2003 and December 2011 and admitted to a level III neonatal unit with International Statistical Classification of Diseases and Related Health Problems, 10th Revision diagnoses P20, P21, P90 and/or P91, and a clinical picture compatible with asphyxia/HIE. Outcome measures were clinical characteristics during neonatal admission and survival without cerebral palsy (CP) at 9–10 years. Data were collected from medical records and the Norwegian Quality and Surveillance Registry for CP.Results The admission rate related to perinatal asphyxia was 7.63 per 1000 term/near-term live births and did not change over time. The incidence of HIE increased significantly after the implementation of TH (from 2.69 to 4.21 per 1000 term/near-term live births, incidence rate ratio 1.56 (95% CI 1.06 to 2.34)). Among 255 included infants (62% boys, mean birth weight 3691 g), significantly more infants were diagnosed with HIE after the implementation of TH compared with before (54% vs 36%, respectively, p=0.005). A total of 227 (92%) of 247 infants survived without CP, with no difference between the time periods. Among infants with moderate/severe HIE born after the implementation of TH, 20 (67%) of 30 infants were cooled and 80% of cooled and 33% of non-cooled infants survived without CP.Conclusions Admission rates and outcomes were stable during these 9 years, but more infants were reported with HIE after the implementation of TH. Non-cooled infants with moderate/severe HIE born after the implementation of TH had poor outcomes, and early clinical HIE evaluation remains a major challenge.